2008
DOI: 10.1097/rct.0b013e3180683bbe
|View full text |Cite
|
Sign up to set email alerts
|

Findings of Bilateral Coronary to Pulmonary Artery Fistula in 64-Multislice Computed Tomographic Angiography

Abstract: A 63-year-old man, who underwent conventional coronary angiography, because of a finding of a confusing vascular structure, was referred for 64-multislice spiral computed tomography (MSCT). His MSCT showed bilateral coronary-pulmonary artery fistula from both right and left coronary arteries via a dilated fistulous vascular malformation. Considering its reasonably high spatial and temporal resolutions, MSCT is regarded as a valuable technique to clarify the diagnosis in incidentally found equivocal cases of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 20 publications
(14 reference statements)
0
36
0
Order By: Relevance
“…Furthermore, in angiography the projection direction is limited to two-dimensions, and thus, in cases with anomaly or complex cardiac pathology, lesions may be overlooked in some cases. Because of such limitations, in previous studies conducted using angiography, diagnostic misinterpretation has been reported to be up to approximately 50% [10] and prevalence of CPAF might have been underestimated.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, in angiography the projection direction is limited to two-dimensions, and thus, in cases with anomaly or complex cardiac pathology, lesions may be overlooked in some cases. Because of such limitations, in previous studies conducted using angiography, diagnostic misinterpretation has been reported to be up to approximately 50% [10] and prevalence of CPAF might have been underestimated.…”
Section: Discussionmentioning
confidence: 96%
“…Van den Brand et al [3] reviewed the records of 126,595 patients who underwent CAG, including a pediatric population, and reported 62 (0.05%) cases of CAF. The reason for this discrepancy may be the limitations of CAG: cannulating all of the arteries with fistulous origins is technically difficult, and complex configurations of the anomalous vessels and their anatomic relations with adjacent structures can be obscured on 2D fluoroscopic images [5]. Consequently, the prevalence of CAF may have been underestimated.…”
Section: Bmentioning
confidence: 99%
“…Because MDCTA can precisely show complex and multiple coronary fistulas and drainage routes, it is the preferred noninvasive method for evaluating patients with suspected coronary anomalies or ischemia [1,4,[6][7][8]15]. Images with multiplanar reconstruction and 3D volume rendering show cardiac and coronary anatomy and the surrounding structures.…”
Section: Mdct Of Congenital Coronary Artery Fistulasmentioning
confidence: 99%
“…Images with multiplanar reconstruction and 3D volume rendering show cardiac and coronary anatomy and the surrounding structures. Reformations focus on the complex anatomy of the fistula from the origin, course, communications, and termination from any projection angle and thus are roadmaps for planning intervention [4,7,15,16].…”
Section: Mdct Of Congenital Coronary Artery Fistulasmentioning
confidence: 99%
See 1 more Smart Citation